2021
DOI: 10.3389/fmed.2021.615417
|View full text |Cite
|
Sign up to set email alerts
|

CircHIPK3: Key Player in Pathophysiology and Potential Diagnostic and Therapeutic Tool

Abstract: A large number of studies in China and other countries have confirmed that circularHIPK3 (circHIPK3) plays an important role in the pathophysiological processes of various diseases. Through the action of sponge miRNA (miR), circHIPK3 regulates cell proliferation, differentiation, and migration, and plays a key role in disease processes. By referring to a large number of research reports, this article explores the specific functional role of circHIPK3 in fibrotic diseases, cancer, and other diseases. This revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 68 publications
(27 reference statements)
0
16
5
Order By: Relevance
“…We also found high levels of circHIPK3 in MAEC-derived exosomes in an HG condition. circHIPK3 is located on chromosome 11p13, which is involved in medicating a wide range of physiological and pathological processes of cardiovascular disease [ 20 ]. HG can upregulate circHIPK3 expression in retinal EC.…”
Section: Discussionmentioning
confidence: 99%
“…We also found high levels of circHIPK3 in MAEC-derived exosomes in an HG condition. circHIPK3 is located on chromosome 11p13, which is involved in medicating a wide range of physiological and pathological processes of cardiovascular disease [ 20 ]. HG can upregulate circHIPK3 expression in retinal EC.…”
Section: Discussionmentioning
confidence: 99%
“…These included: circEGLN3, linear EGLN3, circABCB10, circSOD2, and circACAD11. We also selected circHIPK3, which is dysregulated in multiple cancer types, including colorectal cancer and gastric cancer (22)(23)(24). We used GAPDH mRNA as an internal control to normalize expression for each candidate RNA marker (25).…”
Section: Qpcr Assays and Data Analysismentioning
confidence: 99%
“…Plenty of studies have demonstrated the biogenesis of circHIPK3 and its vital roles in the progression of multiple human diseases, including cancers, cardiovascular diseases, inflammatory diseases, diabetes mellitus, etc. [ 12 , 13 ]. This review aims to provide a more detailed description of the functions of circHIPK3 and a more comprehensive overview of its diagnostic and therapeutic values in some of the aforementioned diseases.…”
Section: Introductionmentioning
confidence: 99%